2017
DOI: 10.1590/1807-1929/agriambi.v21n11p798-802
|View full text |Cite
|
Sign up to set email alerts
|

Empirical models in the description of prickly pear shoot (Nopal) drying kinetics

Abstract: A B S T R A C TThe objective of this study was to describe the technological process involved in the drying kinetics of fresh-cut prickly pear shoots through numerical and analytical solutions. Shoots of two different prickly pear species were used, 'Gigante' and 'Miúda' . Drying was performed at different temperatures (50, 60, 70 and 80 °C) and weighing procedures were made continuously. The experimental data were expressed as moisture ratio. The Page model showed the best fit to the drying kinetics of minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The parameters of the models adjusted to the experimental data of the water quantity kinetics during the drying of the moringa seed were verified the good representation of the Page model, which obtained the highest coefficients of determination (R 2 ), varying from 0,9197 to 0,9935 and the smaller chi-squares ( ), from 0,1618 to 0,2075 (Table 2). ISSN 2166-0379 2020 Pereira et al (2017a) These results show a good fit to the drying curve as presented in Figure 1, higher than that obtained by the other models. Considering the same criteria, we have the models of Henderson and Pabis (Fig 2) and Lewis (Fig 3) with good representation to the experimental points of the drying curve with R 2 above 0.82 and below 0,6 ( Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…The parameters of the models adjusted to the experimental data of the water quantity kinetics during the drying of the moringa seed were verified the good representation of the Page model, which obtained the highest coefficients of determination (R 2 ), varying from 0,9197 to 0,9935 and the smaller chi-squares ( ), from 0,1618 to 0,2075 (Table 2). ISSN 2166-0379 2020 Pereira et al (2017a) These results show a good fit to the drying curve as presented in Figure 1, higher than that obtained by the other models. Considering the same criteria, we have the models of Henderson and Pabis (Fig 2) and Lewis (Fig 3) with good representation to the experimental points of the drying curve with R 2 above 0.82 and below 0,6 ( Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…Contudo, o modelo que melhor representou a secagem em camada delgada da polpa de pequi para as condições estudadas foi o modelo de Page (R 2 = 0,9999). O modelo de Page também apresentou bom ajuste aos dados experimentais de secagem da polpa de pequi da espécie Coriaceum (SOUSA et al, 2017) e do broto de pera espinhosa (PEREIRA et al, 2017) ambas secas em estufa nas temperaturas de 50, 60, 70 e 80 ºC, apresentando R 2 maior que 0,99.…”
Section: Resultsunclassified
“…In the literature it can find values of k dec for nopal drying using different methods. The values reported by Díaz-Ayala et al (2015) for drying of thin slices of cladode with convective crossflow air were from 1.68 ×10 −4 to 5.75×10 −4 s −1 ; by Pereira et al (2017) for drying prickly pear shoots with forced hot air reported values from 1.77 ×10 −3 to 1.52 ×10 −2 s −1 . Thus, it can be observed that the values found in this work are within the range found in the literature.…”
Section: Drying Periodsmentioning
confidence: 92%
“…The main advantages of drying are a decrease in feedstuff moisture and transport costs, inhibition of the growth of microorganisms, reduction of enzymatic and chemical reactions, and increased shelf life among others. In the literature, a different method of drying on cladodes has been reported: osmoticconvective (Medina-Torres, Gallegos-Infante, Gonzalez-Laredo, & Rocha-Guzman, 2008), forced convection tunnel (López et al, 2009), infrared drying (Touil, Chemkhi, & Zagrouba, 2014), convective transversal flow (Díaz-Ayala, Álvarez-García, & Simá-Moo, 2015), forced air circulation (Pereira et al, 2017), convective-vacuum (Dey et al, 2019). These studies have presented good results for considering drying as an appropriate method to preserve or transform cactus cladode.…”
Section: Introductionmentioning
confidence: 99%